160 The impact of hysteroscopy on the disease course of high grade endometrial carcinoma. (13th November 2020) - Larish, A; Weaver, A; Mariani, A
Abstract : Background: With hysteroscopy, concerns have surfaced regarding intraperitoneal spread of endometrial cancer (EC); no studies have evaluated the effect of hysteroscopy on the disease course of a large series of patients with exclusively high risk histology. Methods: Patients who underwent hysterectomy for grade 3 EC at Mayo Clinic in Rochester, MN between January 2009-June 2016 were included, noting hysteroscopy within 6 months. Follow-up was restricted to five years. Cox proportional hazards models were fit to evaluate associations between hysteroscopy exposure and progression. Results: Among 831 patients, 133 underwent hysteroscopy. Patients with versus without hysteroscopy did not differ in mean age (67.7 vs. 67.8 years), BMI (31.6 vs. 31.3 kg/m2), ASA ≥3 (35.3% vs. 38.3%), or serous histology (47.4% vs. 48.7%). Advanced disease (III/IV) was less common among hysteroscopy patients (30.1% vs 43.8%, p=0.003). No difference was observed between those with hysteroscopy versus without (all p>0.05) in positive cytology (22.0% [26/118] vs. 29.7% [191/643]), stage IV disease (16.5% [22/133] vs. 21.9% [153/698]), any positive cytology OR adnexal invasion OR stage IV (28.6% [38/133] vs. 36.1% [252/698]), the aforementioned OR peritoneal recurrence within 2 years (30.8% [41/133] vs. 39.3% [274/698]). After stratifying by stage, hysteroscopy did not increase risk of progression (HR 1.06, 95% CI 0.59–1.92 for stage I/II; HR 0.96, 95% CI 0.62–1.48 for stage III/IV). Conclusion: In this retrospective study of high grade EC, we did not observe any significant association between pre-operative hysteroscopy EC and incidence of positive cytology, peritoneal disease, or progression.